Research of Pipe Cutting and Support in the Pipe-Roof Pre-Construction Method - Yang, Xian; Liu, Yang; Li, Yongsuo; Yang, Zeyu (Frontiers in Earth Science, 2022)
The studies on the steel pipe cutting and support stage in the Pipe-roof Pre-construction Method (PPM) are rare, and their design lacks relevant standards, which is relatively conservative. Based on the Xinleyizhi Station of Shenyang Metro construction case, MIDAS/GTS is used to study the stress of the original jacking steel pipes, supporting column, and surface subsidence under the influence of different construction parameters in the steel pipe cutting and support process in the PPM. The measured data are consistent with the numerical simulation results, which verifies the reliability of the numerical simulation results. With the increase of the distance between support columns , the maximum Mises stress of the original jacking steel pipe, the axial force of the support column, and the ground settlement gradually increases in a specific range. This indicates that the original design scheme can be optimized.